2014
DOI: 10.1002/alr.21277
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐inappropriate antibiotic therapy decreases quality of life improvement after sinus surgery

Abstract: Background Despite their widespread use, antibiotics have not been shown to improve chronic rhinosinusitis (CRS) outcomes. We aimed to determine whether culture-inappropriate postoperative antibiotic therapy was associated with less quality of life (QOL) improvement following functional endoscopic sinus surgery (FESS). Methods This retrospective cohort study recruited 376 adult CRS patients undergoing FESS between 10/1/2007 to 12/31/2011. Patient demographics, comorbidities and medications were collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…A prior study suggested that in the short term, patients who receive culture‐inappropriate antibiotics have less QOL improvement based on change in SNOT‐22 score compared to those who receive culture‐appropriate antibiotics . However, this difference was insignificant after a 6‐month follow‐up.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A prior study suggested that in the short term, patients who receive culture‐inappropriate antibiotics have less QOL improvement based on change in SNOT‐22 score compared to those who receive culture‐appropriate antibiotics . However, this difference was insignificant after a 6‐month follow‐up.…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Zhang et al., only 7% of patients treated empirically with trimethoprim/sulfamethoxazole and clindamycin were found to have culture‐inappropriate antibiotics. This is far less than 2 other studies that reported a 51.4% and 77% change in antibiotics based on culture results .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, history of prior FESS was not significantly associated with the changes of SNOT-22 scores in our study, which was consistent with our previous study. 27 Smith et al 26 found patients undergoing primary surgery were significantly more likely to improve on the QOL measured by RSDI and CSS after an average of 17.4 months postoperative follow-up. The differences in our findings can be due to many reasons, such as the different QOL instruments, different clinical factors collected and evaluated as potential confounders, and different lengths of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction culture‐directed antibiotics have demonstrated improvement in quality of life measures in patients with CRS. Additionally, previous studies have demonstrated the importance of postoperative antibiotic adjustment based on culture results to facilitate recovery following ESS . This study did not seek to evaluate the effect of antibiotic treatment on long‐term effect of culture‐directed antibiotic treatments on patients’ clinical course.…”
Section: Discussionmentioning
confidence: 99%